E-Health Readiness Assessment Framework in Iran - M Rezai-Rad; R Vaezi; F Nattagh (Tehran University of Medical Sciences, 2012)
Background: Concept of e-readiness is used in many areas such as e-business, e-commerce, e-government, and ebanking.In terms of healthcare, e-readiness is a rather new concept, and is propounded under the title of Ehealthcare.E-health readiness refers to the readiness of communities and healthcare institutions for the expectedchanges brought by programs related to Information and communications Technology (lCT). The present research is conducted aiming at designing E-health Readiness Assessment Framework (EHRAF) in Iran.Methods: The e-health readiness assessment framework was designed based on reviewing literature on e-readiness assessment models and opinions of ICT and health experts. In the next step, Delphi method was used to develop and test the designed framework. Three questionnaires developed to test and modify the model while determining weights of the indices; afterward they were either sent to experts through email or delivered to them in face.Results: The designed framework approved with 4 dimensions, 11 constituents and 58 indices. Technical readiness had the highest importance coefficient (0.256099), and the other dimensions were of the next levels of coefficient importance: core readiness (0.25520), social communication readiness (0.244658), and engagement readiness(0.244039).Conclusion: The framework presents the movement route and investment priorities in e-health in Iran. The proposed framework is a good instrument for measuring the e-readiness in health centers in Iran, and for identifying strengths and weaknesses of these centers to access ICT and its implementation for more effectiveness and for analyzing digital divide between them, as well.